Capital Planning for Community Banks : How to organize and manage a capital planning program - Regulatory Compliance Associates, Inc. (Illinois : Banker's Publishing Company, 1990)
This workbook provides insight and direction for bank management's dealing with capital planning. The focus is geared on two levels: The macro sections provide the reader with concepts and ideas while the micro sections literally walk the reader through a risk-based capital policy.
Includes bibliographical references
osc 14/8/17
Loans
Keywords: Banking